The Effectiveness of Social Media Utilization in Learning at Elementary School - Vinnie, Gita; Muktiarni, M; Mupita, Jonah (LPPM Universitas Jenderal Achmad Yani, 2021)
The learning process of students in Indonesia has changed after the Covid-19 pandemic that originated in Wuhan, China and has almost spread to all regions of the world. The government has decided to limit social activities, call for social distancing, and avoid crowds. This is done in order to reduce the spread of the Covid-19 virus in Indonesia. The impact of such condition on education in Indonesia, learning that initially took place face-to-face now has to be done online. This paper describes the effectiveness of using social media platforms such as YouTube in online learning for elementary school students during online learning. The activity is in the form of providing Indonesian language materials through online media to elementary school students of SD 247 Sukapura, Bandung. The results of the activity show that the use of social media in learning can improve the digital literacy of elementary school students. Based on the questionnaires which distributed to the students showed an increase in understanding after being given learning materials through the Zoom application and using social media such as YouTube.